Brazilian travestis, sex workers and migrants. Body, culture and performativity; Epistemology of the political production of transgression and subordination - Luís, Francisco José Silva do Amaral (Seven Editora, 2024)
Borders, as symbolic delimitations that filter relations between subjects and groups of subjects, always fulfill a political function; to delimit, within the scope of these relations, the hierarchization of social actors/actresses and their bodies, according to a certain policy of sexes, genders, social class, race, color, ethnicity or geographical origin. The aim of this text is to demonstrate how body and culture, through performativity, are simultaneously objects and agents of their production as illegal or normalized, giving rise to the emergence of subjects in interaction. To this end, we will resort to an analysis that establishes a parallelism between gender and geographical migrations, seeking to demonstrate how the processes of border crossing, in both cases, present similarities that allow us to apply their analytical grids to both with a character of symbolic reciprocity. DOI:https://doi.org/10.56238/sevened2024.010-040